An assessment of the quality of reference service at the University of the Philippines Diliman Main Library - Sabat, Elizabeth Manalang 1952- (2000)
On the availability of collection, library users responded to how many books of their need were available during their search. Of the 383 respondents, 24 (7 percent) found all the books they wanted; 112 (29 percent) said that 4 out of 5 of the materials are available; 165 (43 percent) for 3 out of 5 of the books are available; 62 (16 percent) said 2 out of 5 books they were able to access; and 20 (5 percent) declared they located only 1 of the 5 books. The 3 out of 5 books option on the availability of collection gathered the highest number of respondents.
Seven reference service points were included in the study and a total of 383 actual users were sampled for the survey conducted during the first semester of 1998-1999 from January to March, in particular as these were considered the peak periods.
The data gathered were tabulated, tallied, analyzed and interpreted using frequency, percentages and mena ranking.
The results show that 77 percent of the reference interviews were successful. Two hundred ninety-six (296) of the 383 respondents received correct and complete answer. In the Instruction in the Use of Reference Tools/Sources, users gave the highest score of 6 which is still below the acceptable level of 7 on a 10-point scale. Attitudinal success fell off significantly when the reference staff left the clients on their own than providing them with the information needed or searching with them. Accuracy level reported higher answering successs than attitudinal and instruction function of the reference librarians.
The study took into consideration the total environment of references services with the reference librarian as the center of reference desk operations; hence the evaluation was focused on the primary activity of which is personal assistance provided by library staff to users in pursuit of information.
The study used the descriptive-survey method of research following unobtrusive measures wherein the evaluees did not know that they were under observation. Data were collected through observations and answers/feedback of actual users who asked professional help during the period of the study.
The study was an actual observation of one of the major aspects of refernce service, question answering of actual users in the Main Library of the University of the Philippines. It was an effort to see the reality of the kind of service the reference librarian was able to provide, to find out the strengths and weaknesses of reference staff in this vital professional service in a library or information center, the skills and knowledge to find answers or to suggest answer-providing sources and search strategies, the instruction in the use of reference resources, the attitude and way of interacting with the clients as these affect the quality of reference service.
Vita
Thesis (M.L.S.)--University of the Philippines, Diliman.
Keywords: University of the Philippines (Diliman). -- Main Library; Academic libraries -- Reference services -- Philippines -- Quezon City; Reference librarians -- Attitudes. -- Philippines -- Quezon City